TIGA belas : catatan perjalanan studio pertuinjukan sastra / editor Mustofa W. Hasyim, Sukandar, Latief S. Nugraha - Mustofa W. Hasyim; Sukandar; Latief S. Nugraha (Interlude, 2013)
xxii, 201 hlm. : ilus. ; 21 cm